Evaluation of Mental Stress Using Physiological Signals - SUBHANI, AHMAD RAUF (2013)
This research aims at the detection of mental stress using electroencephalogram (EEG) and electrocardiogram (ECG) signals. The proposed scheme works by evaluating physiological variability that occurs in mentally stress and control environments. For acquiring physiological signals, an experimental paradigm was designed to solve mental arithmetic tasks under stress and control conditions. Both experiment conditions had four levels of task and every level was separately analysed for variations in signals.